Relative commutativity degree of some dihedral groups - Abdul Hamid, M. (2013)
The commutativity degree of a finite group G was introduced by Erdos and Turan for symmetric groups, finite groups and finite rings in 1968. The commutativity degree, P(G), is defined as the probability that a random pair of elements in a group commute. The relative commutativity degree of a group G is defined as the probability for an element of subgroup, H and an element of G to commute with one another and denoted by P(H,G). In this research the relative commutativity degree of some dihedral groups are determined.